The management of severe eczema in pregnancy - E Keeling; CH Smith; RT Woolf (Clinical Medicine, 2025)
Atopic eczema (eczema; also known as atopic dermatitis) is a chronic inflammatory skin condition. The burden of eczema can be very substantial with significant itch, skin pain, secondary infection, sleep disturbance and psychological distress. Eczema is common in pregnancy. It is therefore important to offer effective treatment to pregnant women, especially those with moderate to severe disease where the burden is greatest. When eczema cannot be adequately managed with skin-directed approaches such as topical preparations and/or phototherapy, systemic therapy may be required to achieve disease control and requires early input from dermatology specialists. The aim of this short review is to summarise this approach.